Animal models of Huntington's disease and their applicability to novel drug discovery and development. (4th May 2023) - Upadhayay, Shubham; Jamwal, Sumit; Kumar, Puneet
ABSTRACT: Introduction: Huntington's disease (HD) is a progressive neurodegenerative disorder caused by an expansion in the CAG trinucleotide repeat in huntingtin (Htt) gene. The discovery of the HD-causing gene prompted the creation of new HD animal models, proving that mutations in the HD gene are linked to either loss of function of the wild-type (un-mutated) gene or toxic gain in the function of a mutated gene. Areas Covered: Animal models of HD have led to an increased understanding of its pathogenesis and resulted in the discovery of new therapeutic targets/drugs. The focus of this review is on the selection and validation of animal models for HD drug discovery. Furthermore, several drugs tested using various models in the preclinical phase have been compiled to demonstrate the applicability of these HD animal models. Expert opinion: The applicability of animal models for HD drug discovery has been well demonstrated. Nevertheless, despite the enormous progression made to date, the development of drug therapy to completely alleviate disease progression has not been achieved. Most of the pre-clinically tested drugs have shown promising results in alleviating HD-associated neurodegeneration and motor and non-motor symptoms, but only a few of them thrived to produce satisfactory results in the clinical phase. This failure has raised concerns about the selection of HD animal models and species, and new strategies for selection are mandated.